2010
DOI: 10.1063/1.3442491
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh secondary electron emission of carbon nanotubes

Abstract: The secondary electron emission of the tube bodies of single-walled carbon nanotubes is found to be ultrahigh and comparable with that of diamond, when the nanotubes are connected with electron reservoir. Both of semiconducting and metallic nanotubes possess this property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
38
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 17 publications
5
38
2
Order By: Relevance
“…Indeed, it has been proposed that direct interaction with the primary beam should lead to appreciable, although modest, secondary electron emission [127,128]. On the other hand, an abnormally high secondary electron emission yield has also been reported for carbon nanotubes [129]. Our own experiments have revealed that nanotubes have a low secondary electron yield, consistent with the conclusions of [127,128].…”
Section: Secondary Emission From Carbonsupporting
confidence: 81%
“…Indeed, it has been proposed that direct interaction with the primary beam should lead to appreciable, although modest, secondary electron emission [127,128]. On the other hand, an abnormally high secondary electron emission yield has also been reported for carbon nanotubes [129]. Our own experiments have revealed that nanotubes have a low secondary electron yield, consistent with the conclusions of [127,128].…”
Section: Secondary Emission From Carbonsupporting
confidence: 81%
“…We disagree with this argument and reiterate that we believe the experiments/explanations presented by Luo et al in Ref. 2 were not adequate to support a claim of ultrahigh intrinsic SE yield from nanotubes. In summary, the arguments presented in the comment 1 are based on incorrect assumptions and we maintain that the results and conclusions presented in our paper are justified.…”
contrasting
confidence: 66%
“…2 We have already published a detailed comment 3 on the problem of misinterpretation of the experimental data that we believe has led to their conclusion of ultrahigh intrinsic secondary electron (SE) yield. Here, we simply point out that the claim by Luo et al 2 of a large intrinsic SE yield from an individual nanotube under a 1-keV primary beam implies that a primary electron transfers hundreds of eV of energy just crossing one nanotube, which is in direct contradiction to all known energy loss mechanisms. In addition, Luo et al mentioned in their response 4 to our comment: 3 "… we do not disagree that an average energy loss of no less than 80 eV by a primary electron is needed for generating one SE from carbon."…”
mentioning
confidence: 99%
“…1,2 Scanning electron microscopy (SEM) and electron-beam lithography (EBL) are increasingly being used for the characterization and fabrication of CNT-based field-effect-transistors [3][4][5] and stimulated field-emitters. [6][7][8][9] Since electron transport plays a fundamental role in the ultimate performance of these techniques, knowledge of the energy dissipation pattern of low-energy electron beams (0.3-30 keV) in CNT materials becomes of prime importance. Monte Carlo (MC) simulations offer a valuable tool for investigating energy-transfer phenomena in irradiated solids.…”
mentioning
confidence: 99%